Direct Formation of Luminescent Fine Crystals Based on (Y, Eu)TiNbO6 Complete Solid Solution with High Crystallinity. Issue 8 (13th May 2016) - Hirano, Masanori; Sato, Shingo
Abstract : Luminescent fine crystals of Y1.00− x Eu x TiNbO6, x = 0–1.00 with high crystallinity were directly synthesized by mild hydrothermal method from weakly basic precursor solution mixtures of YCl3, EuCl3, TiOSO4, and NbCl5 . Orthorhombic aeschynite‐type crystals in the range of 0.5–2.0 μm consisting of crystallites with 33–91 nm based on a complete solid solution in the YTiNbO6 –EuTiNbO6 system were hydrothermally formed at 240°C for 5 h. A single phase of as‐prepared aeschynite‐type structure was maintained in all the (Y, Eu)TiNbO6 solid solution after heating at temperatures up to 1000°C for 1 h in air. In the range of composition x ≤ 0.6, the as‐prepared aeschynite‐type (Y, Eu)TiNbO6 solid solutions transformed to a single phase of euxenite structure after heat treatment at temperatures higher than 1100°C–1200°C. The as‐prepared (Y, Eu)TiNbO6 fine crystals in the range of composition x = 0.75–0.90 showed the strongest luminescence in the red spectral region: strong red ( 5 D0 → 7 F2 transition of Eu 3+ ) and weak orange light ( 5 D0 → 7 F1 ) line spectra among the as‐prepared and heat‐treated samples. Another wet chemical synthesis route confirmed the advantage in directly synthesizing the (Y, Eu)TiNbO6 crystals through this hydrothermal method because heating at 1200°C for 1 h in air was necessary for obtaining crystalline (Y, Eu)TiNbO6 with sufficient luminescence intensity in a composition Y0.70 Eu0.30 TiNbO6 from amorphous powders that were formed via co‐precipitation method.